Reducing contamination in the printed circuit board industry for the improvement of the process and human health - Sarges, Simone Ribeiro (2015)
In this work, an electronic manufacturing company is studied in terms of contamination. The aim of this study was to determine contamination problems, along with their causes and sources. Improvements aimed at reducing the contaminants in the process are suggested, and a positive effect is expected in both the defective parts per million (PPM) of the final products and in human health. It is concluded that negative externalities in the form of industrial contamination may be an important subject for future studies, due to the impact in both the final products and human health.